Bakteri Endofit Asal Berbagai Akar Tanaman sebagai Agens Pengendali Nematoda Puru Akar Meloidogyne incognita pada Tomat - Pradana Pandu Ankardiansyah; Abdul Munif; Supramana Supramana (Jurnal Fitopatologi Indonesia, 2016)
Infection caused by root knot nematode (RKN) Meloidogyne incognita may cause yield losses. Little is known regarding the effectiveness of endophytic bacterial group as biocontrol agents of RKN. This research was aimed to obtain endophytic bacteria group from 16 species of plants, which effectively controlled the RKN. Isolation of endophytic bacteria group was conducted using NA 20%, NA 50%, TSA 20%, TSA 50%, and King’s B medium. All of the bacteria groups giving negative result in hypersensitive and haemolytic tests, was further examined for their ability to produce protease, chitinase, and cyanide acid. The same endophytic bacteria groups were also tested for their potential to control juvenile 2 of M. incognita on tomatoes by seed treatment and soil drenching. Agronomical and pathological traits were observed 40 days after nematodes infestation. Eighty endophytic bacteria groups were successfully isolated and 17 of them were considered potential. Physiological test showed that 16 groups of endophytic bacteria can produce protease enzyme, 12 groups can produce chitinase enzyme, and 5 groups can produce cyanide acid. Specific endophytic bacteria group, i.e. TmtN5 from roots of tomato plant, is the most effective isolate for suppressing root damage and population of RKN. This group was effective as biocontrol agents of RKN because it produceds chitinase, protease, and cyanide acid. This research provided a new information regarding the potential use of endophytic bacteria group as a biocontrol agent of RKN.